Socioeconomic determinants of pediatric asthma emergency department visits under regional economic development in western New York. (February 2019) - Eum, Youngseob; Yoo, EunHye; Bowen, Elizabeth
Abstract: Although the links between asthma in children and physical environmental factors have been well established, the role of community-level socioeconomic status remains inconclusive. Consequently, little attention has been paid to the dynamic changes in the associations between socioeconomic status and asthma outcomes due to structural changes in the community, such as an influx of financial resources. This study examined the relationship between community-level socioeconomic status indicators and asthma-related emergency department utilization for school-aged children in 2011 and 2015, assessing the early impact of a large-scale regional economic development project in western New York, United States. Our analyses controlled for other community-level health risk factors, such as environmental exposure, and spatial correlation of the emergency department usage data. Results indicated that both median household income and health insurance coverage were key socioeconomic predictors of the children's asthma-related emergency department utilization over the study period. We also found that the risk of emergency department utilization for asthma decreased significantly in the area in which regional economic development projects were completed during the initial stage of the project. Through a comparison study we demonstrated that the spatial correlation present in asthma-related ED utilization improved model fit and corrected biases in the estimates. Although our findings suggest that improving the socioeconomic status of communities contributes to a reduction in emergency department utilization for pediatric asthma, more empirical studies are warranted for evaluating the comprehensive effects of regional economic development on public health. Highlights: Median income and health insurance coverage are negatively related to asthma ED use. Regional economic development appears to reduce risk of ED utilization for asthma. Spatial models improve the model fit and the accuracy of inference.